Aspects of reproduction in the West African Dwarf goat - Ngere, L.O.; Mbap, S. (Springer, 1982)
Oestrous cycle and kidding pattern of the West African Dwarf goats were investigated. Data on behavioural oestrus, duration and length of oestrus, the oestrus cycle, time to post-partum oestrus, age at first kidding, influence of season on kidding, frequency of multiple births and its relationship to parity, are included.